Do football players act sustainably? An explorative study focusing on opportunities and limits of sustainable consumption and disposal of football boots - Ludin, Daniela; Avdyli, Fitim; Weiwadel, Tom; Mueller, Erika; Wellbrock, Wanja (Oeconomica Jadertina, 2026)
Football is by far the most popular sport in the world. To pursue this passion, players need the right equipment. The most fundamental utensils needed are football boots. Which football boots are the right ones, every player decides for himself. This study aims to investigate how sustainable is such a football boot from consumption to disposal. Furthermore, the aim of this study is to identify if the idea of sustainability in general has already become established in football. The theoretical background is set by the scientific fields of sports, fast fashion and sustainable consumption. An explorative survey of football players of two amateur football clubs in Southern Germany was executed to generate an overview on purchasing and disposing behaviour concerning football boots. Results show, that players of both football clubs are not very sustainably oriented. The vast majority dispose of their football boots in the trash rather choosing sustainable options. Similarly, not enough attention is paid to environmentally friendly aspects such as sustainable packaging or ecological material when buying. Most players hardly pay attention to these criteria. They pay more attention to comfort criteria such as appearance or fit. This is also reflected in the respondents' prioritization of sustainability. However, the majority of both clubs ensure a longer product life cycle through care and by using their foot-ball boots for a long time.
Keywords: Football Boots, Football Players, Football, Sports, Sustainable Consumption, Sustainability